2011
DOI: 10.1007/s10562-011-0627-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Silica-Supported Cobalt Catalysts Prepared by Decomposition of Nitrates Using Dielectric-Barrier Discharge Plasma

Abstract: Low temperature decomposition of precursors usually leads to higher cobalt dispersion. In this study, we present a method to decompose cobalt precursors by using dielectric-barrier discharge (DBD) plasma without requiring a thermal calcination process. Cobalt (Co) catalysts prepared by DBD plasma were characterized by a range of techniques. The results indicate that the DBD decomposition method can not only reduce the decomposition time but also achieve an increased Co dispersion, small Co 3 O 4 cluster size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Due to the 20 kHz AC voltage applied, the temperature of the catalyst bed during the plasma treatment was 527 • C. The average pore size of the catalyst decreased from 9.8 to 6.9 nm, and Ni nanoparticles as small as 5 nm were obtained, providing higher nickel dispersion, improved anti-coke performance, and higher conversion of CH 4 (from 80.3 to 94.2%) and CO 2 (from 64.4 to 73.8%) in dry reforming of methane. A similar correlation between average pore size and reactant conversion was noticed by Huang et al (2011) and Tang et al (2015). Karuppiah and Mok (2014) applied an AC DBD plasma of 11-12.5 kV (operating frequency: 1 kHz) in a 20%H 2 /Ar atmosphere to reduce Ni/γ-Al 2 O 3 catalyst, obtaining highly active ultrafine Ni nanoparticles with uniform dispersion after 4 h of reduction.…”
Section: Plasma Calcination and Reduction Of Supported Metal Catalystssupporting
confidence: 71%
“…Due to the 20 kHz AC voltage applied, the temperature of the catalyst bed during the plasma treatment was 527 • C. The average pore size of the catalyst decreased from 9.8 to 6.9 nm, and Ni nanoparticles as small as 5 nm were obtained, providing higher nickel dispersion, improved anti-coke performance, and higher conversion of CH 4 (from 80.3 to 94.2%) and CO 2 (from 64.4 to 73.8%) in dry reforming of methane. A similar correlation between average pore size and reactant conversion was noticed by Huang et al (2011) and Tang et al (2015). Karuppiah and Mok (2014) applied an AC DBD plasma of 11-12.5 kV (operating frequency: 1 kHz) in a 20%H 2 /Ar atmosphere to reduce Ni/γ-Al 2 O 3 catalyst, obtaining highly active ultrafine Ni nanoparticles with uniform dispersion after 4 h of reduction.…”
Section: Plasma Calcination and Reduction Of Supported Metal Catalystssupporting
confidence: 71%
“…After the process of Co 3 O 4 →CoO, higher cobalt dispersion may promote the interaction between CoO and the support, as well as the formation of cobalt silicate, which resulted in a decreased reducibility of the Co/SiO 2 P catalyst [13,21,22]. Huang et al [7,9] have found a coincident conclusion that lasma-assisted Co-based catalysts were more difficult to be reduced than catalysts prepared by the traditional calcination method. The TPR profile of the Co/Zr/SiO 2 P catalyst is nearly the same as the TPR profile of the Co/SiO 2 P. The only difference is that the peak of CoO→Co 0 for Co/Zr/SiO 2 P is shifted to a lower temperature and the peak area over 670 • C decreased.…”
Section: Textual Properties Of Catalystsmentioning
confidence: 99%
“…In the following years, we could observe a significant growth of interest in employing cold plasma in the conventional catalyst preparation at various stages of this procedure [22][23][24][25][26][27][28][29][30][31][32][33][34]. These methods involve plasma initial decomposition of precursors, plasma replacement of calcination and reduction processes, plasma pretreatment of supports, as well as plasma breaking of thin films to form specific nano-sized catalysts.…”
Section: Plasma-enhanced Preparation Of "Conventional" Catalystsmentioning
confidence: 99%